Christine Cristina - Sandrelli, Amanda; Boni, Alessio 1966-; Haber, Alessandro 1947- (CG Home Video S.R.L., 2010)
Explores the life of Christine de Pisan, the Venetian-born poet of the 15th century, who spent most of her life at the court of Charles V in Paris
Keywords: Christine / de Pisan / approximately 1364-approximately 1431 / Drama; Authors, French / To 1500 / Drama; Women authors, French / To 1500 / Drama; Italian language / Films for Italian speakers; DVD-Video